Measuring customer satisfaction of service quality by fuzzy evaluation approach - Firdawati Mohamed,; Suriana Alias,; Mariam Setapa,; Siti Farah Haryatie Mohd Kanafiah,; Liziana Kamarulzaman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Service quality plays an essential part in customer satisfaction. There are many approaches to measure customer satisfaction through delivery of service quality. One of the issue that leave the decision maker in an awkward position in selecting the most appropriate criteria available is by customer satisfaction. Therefore, the purpose of this study is to evaluate the customer satisfaction of service quality by using advanced methods; fuzzy evaluation approach. The service quality selected is based on five criteria, which are tangible, responsiveness, assurance, empathy, and reliability. The linguistic term of each criterion is used to get the best evaluation result. The developed questionnaire is distributed to twenty experts in the service quality at Jabatan Hal Ehwal Agama Islam Kelantan (JHEAIK) for one day duration. The findings showed that all the criterias meet the high level of service quality with the level satisfaction in between 0.6 and 0.8. The lowest ranking level of satisfaction are Responsiveness (C2) and Reliability (C5). Meanwhile, Tangible (C1) and Empathy (C4) are the the middle value of customer satisfaction. Lastly, with the highest value of level satisfaction which is Assurance (C3). The outcome of the study will help to increase customer satisfaction at JHEAIK by improving their management service quality according to each criteria. Therefore, the fuzzy evaluation is a powerful approach to evaluate the criteria level for customer satisfaction in service quality.